Case Report: PD-1 Inhibitor Is Active in Lung Adenocarcinoma With B Cell Deficiency - Yuan, Shumin; Hu, Xiufeng; Zhao, Yanqiu; Wang, Zibing (Frontiers in Immunology, 2020)
Introduction: In murine cancer models, B cells are unnecessary for efficacy of PD-1 inhibitor. However, we do not know whether this applies to clinical settings, especially in patients with non-small-cell lung carcinoma (NSCLC). Case presentation: We report on the case of an advanced lung adenocarcinoma patient without oncogenic driver mutations whose disease progressed on second-line bevacizumab-containing chemotherapy regimens. These previous treatments resulted in profound thrombocytopenia and increased number of B cells; both effects were hard to alleviate. The patient was diagnosed with marginal zone B-cell lymphoma by flow cytometry immunophenotyping. After five cycles of rituximab in combination with lenalidomide treatment, the percentage of B cells rapidly declined to undetectable levels and the lymphoma regressed completely. However, because masses in the lung gradually increased, this patient was subsequently treated with a PD-1 inhibitor. The patient’s condition stabalized, and the mass shrank to reach partial response, with progression free survival exceeding 15 months and no serious adverse events. Conclusion: The present case proves the efficacy of PD-1 inhibitor in metastatic lung adenocarcinoma in the absence of B cells. Immune checkpoint inhibitions are thus a choice for patients with B cell deficiencies, such as X-linked agammaglobulinemia, immunoglobulin deficiencies, and common variable immunodeficiency, diseases that have historically been excluded from clinical trials for oncologic drugs.